MAMs Protect Against Ectopic Fat Deposition and Lipid-Related Kidney Damage in DN Patients - Yang, Ming; Han, Yachun; Luo, Shilu; Xiong, Xiaofen; Zhu, Xuejing; Zhao, Hao; Jiang, Na; Xiao, Ying; Wei, Ling; Li, Chenrui; Yang, Jinfei; Sun, Lin (Frontiers in Endocrinology, 2021)
Ectopic fat deposition (EFD) in the kidney plays a key role in the development of diabetic nephropathy (DN). Mitochondria-associated ER membranes (MAMs) are structures that connect to the endoplasmic reticulum (ER) and are involved in lipid metabolism. However, there are few studies on MAMs in the field of kidney disease, and the relationship between EFD and MAMs in DN is still unclear. In this study, increased EFD in the kidneys of DN patients was observed, and analysis showed that the degree of EFD was positively correlated with renal damage. Then, the MAMs were quantified by an in situ proximity ligation assay (PLA). The MAMs in the kidneys were found to gradually decrease through the different stages of DN, while the expression of ADRP (a marker of lipid drops) and tubulointerstitial damage increased. Moreover, correlation analysis showed that the MAMs were negatively correlated with serum lipid levels, the EFD in the kidney and renal damage. Finally, we observed decreased expression of MAM-control proteins (DsbA-L, PACS-2 and MFN-2) in different stages of DN and they were associated with lipid deposition and renal damage. These data showed that the destruction of MAMs in DN might be the cause of EFD and interstitial damage in the kidney.